(untitled) (Research, Society and Development, 2023)
The solvent–steam assisted gravity drainage is an oil recovery process that combines the advantages of thermal and miscible effects, and it has been successfully tested, especially in Canada, where many heavy oil reservoirs are located. This method uses two parallel horizontal wells drilled one above the other, the upper injects steam and solvent and the lower produces oil. This process has not been applied yet in Brazil, where there are heavy oil reservoirs, especially in northeast region. Based on this context, this research aimed to study the application of the ES-SAGD process in a semisynthetic reservoir, with characteristics similar to those found in the Brazilian Northeast, specifically to analyze the influence of the solvent injection scheme on ES-SAGD. Numerical simulations were performed using commercial software from CMG. It was analyzed several steam-solvent injection rates, using two injected temperatures for solvent, (at reservoir or at steam temperature´s), in order to minimize explosion risks, that can be due to high temperatures. Results showed that solvent injection temperature has great influence on oil recovery, it is better for oil production when it is inject hot solvent, because cold solvent generates a cooling of the steam. However, it is possible to injected cold solvent (at reservoir temperature), and increase oil production, changing some steam properties, avoiding explosions risks.